2015
DOI: 10.2298/tsci130603051h
|View full text |Cite
|
Sign up to set email alerts
|

Experimental approach to investigate the dynamics of mixing coolant flow in complex geometry using PIV and PLIF techniques

Abstract: The aim of this work is to investigate experimentally the increase of mixing phenomenon in a coolant flow in order to improve the heat transfer, the economical operation and the structural integrity of Light Water Reactors-Pressurized Water Reactors (LWRs-PWRs). Thus the parameters related to the heat transfer process in the system will be investigated. Data from a set of experiments, obtained by using high precision measurement techniques, Particle Image Velocimetry and Planar Laser-Induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Schikorr et al [14] improved Rehme's correlation include grid spacers with mixing devices based on new pressure drop measurements. Morovere, recent studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] have reported that the mixing vanes cause cross and THERMAL SCIENCE: Year 2019, Vol. 23,No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schikorr et al [14] improved Rehme's correlation include grid spacers with mixing devices based on new pressure drop measurements. Morovere, recent studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] have reported that the mixing vanes cause cross and THERMAL SCIENCE: Year 2019, Vol. 23,No.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this effect has to be taken into account in VVER assembly head calculations. Hutli et al [26] investigated experimentally the increase of mixing phenomenon in a coolant flow in order to improve the heat transfer, the economical operation and the structural integrity of VVER-440 using PIV and PLIF techniques. They obtained detailed information on the velocity, turbulence and temperature distribution for parallel turbulent flows through sub-channels of a hexagonal VVER-type rod bundle.…”
Section: Introductionmentioning
confidence: 99%
“…[1], [2], [3], [4], [5]) results the necessity for attention to the effect of water sucked from perforations in central tube on temperature and velocity profile at the position of thermocouple designed to measured temperature at the fuel assembly outlet. Manufacturing of the second physical model of the fuel assembly is prepared in our faculty.…”
Section: Introductionmentioning
confidence: 99%